PERANAN SEKTOR PUBLIK LOKAL DALAM PERTUMBUHAN EKONOMI REGIONAL DI WILAYAH SURAKARTA (1987-2000) - Rahayu, Siti Aisyah Tri (KINERJA, 2004)
This paper’s aim is to explain the role of the local public sectors in regional economic growth in Ex-Residency of Surakarta. The question we ask in this paper is whether local taxes and local expenditures affect regional economic growth in Ex Residency of Surakarta. This question is very important in two respect. First, It would be especially interesting to know whether local government taxes and/or expenditures have had an impact on regional economic growth. An alternative view argues againts any such impact. Second, as local autonomy will soon be granted, local government need to understand the mechanism by which local taxes and expenditures affect the regional economy.The major finding in this paper area as follows. The role of local government in regional economic growth has been very significant. Local taxes and local revenues have a significant negative effect on local regional economic growth, while local government investment have a significant positive effect on regional economic growth. On the other hand, Local government consumption and labor force have no significant effect on regional economic growth. One of the crusial policy implication of this paper is that we must enhance the role of local government, local autonomy having been recently introduced. More specifically, the central government should transfer more revenue sources to its lower level local government through. For example, revenue sharing of national taxes.Keywords: local public sector, regional economic growth, regional economic gap.